IMPLEMENTATION OF FRANCHISE AGREEMENT PERSPECTIVE IN CONTRACT LAW - Lina Maulidiana (University of Sang Bumi Ruwa Jurai, 2017)
Franchise is one form of growing business activity in Indonesia, where the agreement based on principle of freedom of contract. This study aims to analyze of the franchise agreement implementation in contract law perspective, and factors inhibiting and supporting the franchise agreement in the contract law perspective. This research is a qualitative study using a non-doctrinal approach to socio-legal research, in order to get an overview of study subjects to find an ideal reconstruction of the franchise in the contract law perspective. An approach that is non-doctrinal with presumption that the object of the law is interpreted as part of a social sub-system among other social sub-systems. The study also includes three stages, namely the study of philosophy which focuses on literature, study of normative to see how legislation to regulate legal relationships in the franchise business and was associated with the values of philosophy and conducted cross-checking through interviews with actors then do a sociological study to find in-put of justice sought. It concluded that the franchise is a document legal agreement between the franchisor and franchisee (about the rights and obligations). Achievement in the agreement that gives something include the obligations of Franchisor to provide flexibility to run the business without interruption to franchisee for a certain period, the principles of business management following intellectual property rights such as trademarks, logos, patents, and other, which is part of the business concept franchise, for the franchise fee as agreed in the agreed amount. If the agreement between the parties is not carried out for example franchisee does not pay a franchise fee to the franchisor, it may be requested compensation. In an agreement is possible non-performance of the agreement, although the terms of validity of the agreement have been fulfilled. It caused by uncommitment (breach of contract) and coercion or force majeure. Therefore in the agreement, must have a balance between the rights and obligations between both parties that the franchisor and franchisee.